Intra-arterial Administration of Human Umbilical Cord Blood Derived Cells Inversed Learning Asymmetry Resulting From Focal Brain Injury in Rat - Gornicka-Pawlak, Elzbieta; Janowski, Miroslaw; Habich, Aleksandra; Jablonska, Anna; Sypecka, Joanna; Lukomska, Barbara (Frontiers in Neurology, 2019)
Background: Focal brain injury is a leading cause of serious disability significantly worsening patients’ quality of life. Such damage disrupts the existing circuits, leads to motor and cognitive impairments as well as results in a functional asymmetry. To date, there is still no therapy to effectively restore the lost functions. We examined the effectiveness of human umbilical cord blood (HUCB)-derived cells after their intra-arterial infusion following focal stroke-like brain damage. Methods: The model of stroke was performed using ouabain stereotactic injection into the right dorsolateral striatum in rats. Two days following the brain injury 107 cells were infused into the right carotid artery. The experimental animals were placed into enriched environment housing conditions to enhance the recovery process. Behavioral testing was performed using a battery of tasks visualizing motor as well as cognitive deficits for 30 days following brain injury. We assessed animal asymmetry while they were moving forward at time of testing in different tasks. Results: We found that intra-arterial infusion of HUCB-derived cells inversed lateralized performance resulting from the focal brain injury at the early stage of T-maze habit learning task training. The inversion was independent from the level of neural commitment of infused cells. The learning asymmetry inversion was observed only under specific circumstances created by the applied task design. We did not found such inversion in walking beam task, vibrissae elicited forelimb placing, the first exploration of open field, T-maze switching task as well as apomorphine induced rotations. Both the asymmetry induced by the focal brain injury and its inversion resulting from cell infusion decreased along the training. The inversion of learning asymmetry was also independent on the range of the brain damage. Conclusions: Intraarterial infusion of HUCB-derived cells inversed lateralized performance of learning task resulting from focal brain damage. The inversion was not visible in any other of the used motor as well as cognitive tests. The observed behavioral effect of cell infusion was also not related to the range of the brain damage. Our findings contribute to describing the effects of systemic treatment with the HUCB-derived cells on functional recovery following focal brain injury.